(untitled) (Praxis Educativa, 2024)
This article is an exercise of de/re-composition of the experience of the opening course of the curricular space “Práctica Profesional” corresponding to the fifth year of the Teacher Education Program in Education Sciences of Humanities School at Universidad Nacional de Mar del Plata. It is an account of the development of the proposal, including contextual conditions, definitions, and criteria that guided the movement that meant the implementation of the subject that serves as a corollary of the course. Throughout the story, the paper characterizes the subject within the framework of the teacher’s curriculum, explains the theoretical and methodological foundations that support the proposal, and describes the training devices that have been designed considering the contextual conditions in which the course took place.